Dom Quixote à luz da análise do discurso de Michel Pêheux - Almeida, Raimundo Batista (2013)
This study is an analysis of discursive clippings of Chapters II, III, IV, V and VIII of Volume I in Don Quixote de la Mancha by Miguel de Cervantes. The choice of this work was made because it is the most important of Spanish literature, and moreover, an important fiction book of world literature. Therefore, we based on several works of Cervantes scholars, among them Basanta, Rico and Riquer; leaders of commemorative editions of 400 years of the work in study. The boldness of this work is to understand the work in question, from the perspective of discourse analysis of the French line, theory and device of the analysis in study. We emphasize that the theory was founded by Michel Pecheux, in France, in the late sixties and developed in Brazil by Eni Orlandi and followers. Thus, the study aims to examine some specific discursive segments of a few chapters of Volume I in the above mentioned work. It aims specifically, to identify effects of interdiscourse, discursive, ideological and imaginary formations in the cutouts as well as to establish approaching between Don Quixote and Discourse Analysis. The analyzes indicate that Don Quixote the knight’s speech creates the effect of combating social injustice and that Cervantes worked with the novels of chivalry in the form of humor, aiming to pass by the Inquisition without censorship. We so conclude the thesis stating that this work does not end here, and must be deepened in future doctoral studies and scientific articles. Likewise, we hope it will be a path for further research, involving Discourse Analysis and literature.